2007
DOI: 10.1158/0008-5472.can-06-4594
|View full text |Cite
|
Sign up to set email alerts
|

GRP78/BiP Inhibits Endoplasmic Reticulum BIK and Protects Human Breast Cancer Cells against Estrogen Starvation–Induced Apoptosis

Abstract: The recent development of hormonal therapy that blocks estrogen synthesis represents a major advance in the treatment of estrogen receptor-positive breast cancer. However, cancer cells often acquire adaptations resulting in resistance. A recent report reveals that estrogen starvationinduced apoptosis of breast cancer cells requires BIK, an apoptotic BH3-only protein located primarily at the endoplasmic reticulum (ER). Searching for novel partners that interact with BIK at the ER, we discovered that BIK selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
258
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(271 citation statements)
references
References 45 publications
11
258
0
2
Order By: Relevance
“…Occupancy of the Src SH2 domain is thought to result in the activation of Src, suggesting a role for FAK upstream of Src. 24 We discovered that by mediating TFII-I tyrosine phosphorylation at Tyr248, Src is involved in CD147-induced TFII-I activation, and the consensus tyrosine phosphorylation site at residue 248 is required for TFII-I stimulation of the ERSE, which is consistent with previous findings. 27 Tumor progression may occur as the result of anti-apoptotic mechanisms combined with a general tolerance to suboptimal microenvironmental conditions as a result of the cytoprotective components of the UPR.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Occupancy of the Src SH2 domain is thought to result in the activation of Src, suggesting a role for FAK upstream of Src. 24 We discovered that by mediating TFII-I tyrosine phosphorylation at Tyr248, Src is involved in CD147-induced TFII-I activation, and the consensus tyrosine phosphorylation site at residue 248 is required for TFII-I stimulation of the ERSE, which is consistent with previous findings. 27 Tumor progression may occur as the result of anti-apoptotic mechanisms combined with a general tolerance to suboptimal microenvironmental conditions as a result of the cytoprotective components of the UPR.…”
Section: Discussionsupporting
confidence: 91%
“…These results further confirm the conclusion that CD147 is a cancer biomarker. 24 While the expression of the ER-resident chaperone Bip was undetectable by immunohistochemistry in all 42 normal liver tissue samples (Table 1a), Bip was expressed in the majority of the 98 hepatoma tissues (83.7%; Table 1a). These results reveal that Bip is highly elevated in human HCC tissues compared with normal liver tissues (Z ¼ À 7.179, P ¼ 0.000), which suggested that the UPR is activated in human HCC tissues.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, GRP78 can suppress EnR stress-induced apoptosis by sequestering caspase-7 and inhibiting its activation [84,85]. GRP78 can also inhibit proapoptotic protein BIK [86]. There may also be a contribution from growth factor receptor (GFR) signalling to GRP78 overexpression-induced resistance, since membrane-bound GRP78 can activate RAS-MAPK and PI3K -AKT pathways in other cells [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…The plasmid pcDNA3/His-Grp78 has been previously described. 38 Antibody against LC3 was either a gift from Dr. R Kopito (Stanford University, Stanford, CA) or purchased from MBL International. Antibodies used for western blot analysis include Beclin1 (goat polyclonal IgG for immunoprecipitation, Santa Cruz Biotechnology; mouse monoclonal IgG for blotting, BD Pharmingen), phospho-JNK1 (mouse monoclonal IgG, Promega), PI3KC3 (rabbit polyclonal IgG, Invitrogen), b-actin (AC15, mouse IgG, Sigma); CHOP (B3, mouse IgG1), ATF4 (rabbit polyclonal), JNK1 (rabbit polyclonal IgG) and XBP-1 (rabbit polyclonal) from Santa Cruz Biotechnology; phospho-eIF2a (rabbit polyclonal IgG) and eIF2a (rabbit polyclonal IgG) from Cell Signaling Biotechnology; GRP78 (mouse monoclonal IgG) from BD Pharmingen; GRP78 (rabbit polyclonal antiserum), GRP94 (rat monoclonal IgG) and KDEL (mouse monoclonal IgG) from Stressgen.…”
Section: Methodsmentioning
confidence: 99%